(untitled) - Purpura, Philip P. (Amsterdam,Boston, 2007)
The book explains practical issues, handled by senior government officials, first responders and private security practitioners. Theory from more than 20 disciplines provides a foundation for the book, including criminal justice, international relations, government, psychology, sociology, military science, business, structural engineering and public health.-Morning News, Florence, SC, January 21, 2007
Keywords: Terrorism,National security,Internal security,Sự khủng bố,An ninh quốc gia; Prevention,Sự ngăn chặn; United States,United States,United States,Hoa Kỳ,Hoa Kỳ